Penegakan Hukum Lingkungan pada Pencemaran Tambak Udang Ilegal di Kabupaten Sumenep - Julia Salsabila Nur Rahman; Neni Ruhaeni (Jurnal Riset Ilmu Hukum, 2025)
Abstract. This research discusses environmental pollution due to illegal shrimp farming in Sumenep District that causes damage to coastal ecosystems such as mangroves, sea water pollution, and decreased fishermen's catch. This phenomenon occurs due to weak supervision, lack of environmental permits, and non-compliance with regional spatial planning. The purpose of the research is to analyze the form of pollution and examine the effectiveness of law enforcement associated with environmental control based on Law Number 32 of 2009 (UUPPLH) and Law Number 11 of 2020 (UUCK). This research uses a normative juridical method with descriptive-analytical specifications. Data were collected through literature study of primary, secondary, and tertiary legal materials, then analyzed normatively-qualitatively. The results show that illegal shrimp ponds have not been subject to strict sanctions and are still dominated by a coaching approach. Law enforcement has not touched the administrative, civil and criminal aspects optimally. It is concluded that the licensing system, supervision, and community empowerment need to be strengthened so that environmental protection goals can be achieved sustainably. Thanks are extended to those who have assisted in the preparation of this work. References used are in the form of laws and regulations and environmental law literature. Abstrak. Penelitian ini membahas pencemaran lingkungan akibat usaha tambak udang ilegal di Kabupaten Sumenep yang menyebabkan kerusakan ekosistem pesisir seperti mangrove, pencemaran air laut, serta menurunnya hasil tangkap nelayan. Fenomena ini terjadi karena lemahnya pengawasan, tidak adanya izin lingkungan, dan ketidaksesuaian dengan tata ruang wilayah. Tujuan penelitian adalah menganalisis bentuk pencemaran dan menelaah efektivitas penegakan hukum dikaitkan dengan pengendalian lingkungan berdasarkan Undang-Undang Nomor 32 Tahun 2009 (UUPPLH) dan Undang-Undang Nomor 11 Tahun 2020 (UUCK). Penelitian ini menggunakan metode yuridis normatif dengan spesifikasi deskriptif-analitis. Data dikumpulkan melalui studi kepustakaan dari bahan hukum primer, sekunder, dan tersier, kemudian dianalisis secara normatif-kualitatif. Hasil menunjukkan bahwa tambak udang ilegal belum dikenakan sanksi tegas dan masih didominasi pendekatan pembinaan. Penegakan hukum belum menyentuh aspek administratif, perdata, dan pidana secara optimal. Disimpulkan bahwa sistem perizinan, pengawasan, serta pemberdayaan masyarakat perlu diperkuat agar tujuan perlindungan lingkungan dapat tercapai secara berkelanjutan. Terima kasih disampaikan kepada pihak-pihak yang telah membantu penyusunan karya ini. Referensi yang digunakan berupa peraturan perundang-undangan dan literatur hukum lingkungan.